1984
DOI: 10.1111/j.1365-2125.1984.tb02549.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta‐adrenoceptor blockade on exercise performance and respiratory response in healthy, physically untrained humans.

Abstract: The effects of propranolol 80 mg orally were compared with those of placebo on the response to a stepwise increasing exercise test in 17 healthy and physically untrained volunteers, of whom eight were female. Propranolol showed no significant effects on maximum work rate or perceived exertion rate. However, submaximal O2 uptake, CO2 output and minute ventilation tended to be lower after propranolol than after placebo. It is concluded that in subjects with a low work capacity, beta‐adrenoceptor blockade does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The principle finding of this paper is to confirm the results of Violante et al (1984) that ,-adrenoceptor blocking drugs reduce minute ventilation at submaximal but not at maximal exercise levels (above 150 watts). In our study the effects were seen most clearly with the cardioselective drug atenolol.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The principle finding of this paper is to confirm the results of Violante et al (1984) that ,-adrenoceptor blocking drugs reduce minute ventilation at submaximal but not at maximal exercise levels (above 150 watts). In our study the effects were seen most clearly with the cardioselective drug atenolol.…”
Section: Discussionsupporting
confidence: 73%
“…The results with propranolol showed the same trend but with more scatter, possibly because of the much greater variation in plasma levels known to occur follow-ing single oral doses of propranolol than with atenolol. However, the fact that Violante et al (1984) used propranolol supports the view that the effect in depressing ventilation is not related to cardioselectivity or lipid solubility. Twentyman et al (1981) also found a tendency (not statistically significant) for VE to be reduced during progressive exercise following propranolol but also found that the effect was time dependent, ventilation being depressed early in submaximal exercise but not as the steady-state is approached.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, beta blockers are a poor choice in patients who wish to engage in an exercise program because they interfere with exercise performance. Most studies have shown that nonselective beta blockade results in a 6-14% reduction in maximal oxygen uptake (V02 max) [1,2], while few studies have reported that beta blockers do not have such an effect [3]. On the other hand, beta l-selective blockade also decreases VO 2 max by 11% [4,5].…”
mentioning
confidence: 99%